2006
DOI: 10.1177/0021998305053459
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Delamination at Ply Drops in Tapered Composites by Ply Chamfering

Abstract: The design of structures is often optimized by gradually decreasing the thickness as the load carrying requirement on the components decreases. Such structures in composites are made of tapered laminates involving dropping of plies. However, these structures are often prone to early delamination initiation, which leads to premature failure of the component and therefore limits its useful life. In the past, many routes to circumvent this problem have been evolved, such as the use of adhesive film layers or inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 13 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…It would normally be assumed that the reduction in strength due to premature failure initiated by delaminations at ply drops would have to be accepted as a feature of the design (so long as no additional wrinkling was present). In the case reported above, the tensile strength with unchamfered plies was 1090 MPa and was 1400 MPa with chamfered plies [13]. the compressive strength with unchamfered plies was 636 MPa and with chamfered plies was 1130 MPa.…”
Section: Failed Sample Showing Multiple Delaminationsmentioning
confidence: 68%
“…It would normally be assumed that the reduction in strength due to premature failure initiated by delaminations at ply drops would have to be accepted as a feature of the design (so long as no additional wrinkling was present). In the case reported above, the tensile strength with unchamfered plies was 1090 MPa and was 1400 MPa with chamfered plies [13]. the compressive strength with unchamfered plies was 636 MPa and with chamfered plies was 1130 MPa.…”
Section: Failed Sample Showing Multiple Delaminationsmentioning
confidence: 68%
“…Many studies have shown that the end part geometry of jointed parts is a key factor affecting the stress distribution in an adhesive joint, and contributes to the overall material strength. 14,15 Additionally, the stacking sequence and orientation angles are other important factors. [16][17][18][19] According to these results, it can be deduced that for the mechanical analysis of a ply splice structure, the junction geometry and the ply angle should also be paid close attention to.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of studies about delamination in tapered areas are considered under quasi-static loadings. 9,10 However, low stress-level fatigue failure analyses are still inaccurate and subjected to uncertainties, because unlike quasi-static tests, slight changes in the fatigue-loading history can significantly change the failure process. 11,12 This haphazardness makes each fatigue failure incident a unique case to be verified experimentally.…”
Section: Introductionmentioning
confidence: 99%